PROTEIN BINDING STUDY OF FELODIPINE USING VALIDATED LIQUID CHROMATOGRAPHIC METHOD - Vijitha, Swarna; Rajavel, P.; Udayasree, K. (International Journal of Current Pharmaceutical Research, 2017)
Objective: The aim of present study was to develop and validate a new simple, easy, selective, precise, accurate reverse phase high-performance liquid chromatography for the estimation of felodipine in bulk and pharmaceutical dosage form. Methods: The separation was carried on HPLC system consisting C18 column (150 mm ×4.6 nm, 5 µm) at room temperature coupled with a phenomenixcolumn silica with flow rate 1 ml/min. The mobile phase used was methanol: acetonitrile in the ratio of 50: 50. The drug was detected using UV-visible detector at the wavelength of 230 nm and run time was 10 min. Results: The retention time was 3.138 min. Linearity was observed in the concentration range of 5-25μg/ml. The accuracy of the method was assessed by percentage recovery studies at three different levels at 80%, 100% and 120% of its working concentration. The percentage recovery of felodipine in the developed method was found to be in the ranges of from 99.81-100.00% that indicates the good accuracy of the method. The percentage % RSD of precision was found to be less than 2%. The method was validated as per ICH guidelines. The developed method was employed in in vitro protein binding studies using semi permeable membrane and performed by plotting calibration curve (peak area vs concentration) the % drug release of felodipine was calculated. Conclusion: The proposed method was found to be simple, precise, accurate and consistent. The validated parameters are statistically validated for linearity, precision and limit of detection, limit of quantification, robustness, ruggedness were concluded.